Nephroprotective effect of the leaves of Murraya koenigii L. Spreng in vivo. - Yankuzo, Hassan; Santosa, Rahajoe Imam; Ahmed, Qamar Uddin; Akter, Seikh Farid Uddin; A.Talib, Norlelawati (2010)
The leaves of Murraya koenigii (Linn.) Spreng (curry leaf) is widely use a nephroprotective agent in Kidney's infirmities among diabetics by the traditional practitioners in Malaysia. However, the latter role of curry leaf has been grossly under reported and is yet to receive proper scientific evaluation. The present study was designed to investigate the beneficial effect of the leaves of M. koenigii (L.) on diabetes-induced renal damage in vivo with regard to prove its efficacy by local traditional practitioners in the treatment of kidney frailties in diabetics. Aqueous (AQ) extract of the leaves of M. koenigii (L.) was administered to both normal and streptozotocin (STZ) induced diabetic male rats (Spraque Dawley strain). Animals were divided into six groups (n=6) and treated with variable dose levels of AQ extract (200&400 mg/kg body weight/day) for 30 days. At the end of 30 days, animals were sacrificed, blood and collected, processed and stored at -70*C for the estimation of serum urea and creatinine, changes in plasma antioxidant capacity by FRAP assay, and lipid peroxidation, in the normal and STZ induced diabetic rats. Histological studies of the Kidneys of these animals were also studied by light microscopy to determine the beneficial effect of leaves. Daily oral administration of variable dose levels of the AQ extract for 30 days, produced significant dose dependant decrease in serum urea and creatinine levels (p<0.001) as well as in the elevated lipid hydroperoxides (p<0.05) in diabetic treated rats compared to the control (non-diabetic) subjects. It also markedly improved plasma antioxidant concentration (p<0.01) in both normal and treated diabetic rats, respectively. However, the normal treated rats showed minimal variation in these parameters in comparison to normal controls. Histological studies of the kidneys of these animals explicitly showed comparable tissue regeneration by the AQ extract. Conclusion: The results of our study scientifically support the traditional belief for using the leaves of M. koenigii (L.) in the treatment of pain disorders related to renal impairments among diabetics.